Parkia bigalandulosa -Mediated Silver Nanoparticle Synthesis: Comprehensive Analysis through UV, IR, SEM, and TEM Techniques (International Journal of Food and Nutritional Sciences, 2022)
The silver nanoparticles, reduced through biological means, exhibited a distinct surface plasmon resonance at 440nm, as evidenced by the UV–visible absorption spectrum analysis. FTIR analysis was employed to identify the compounds responsible for the bio-reduction of silver ions and to elucidate the functional groups present in the leaf extract of P. bigalandulosa. Microscopic studies utilizing Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) further confirmed the spherical shape of the nanoparticles, with an average diameter measuring 15 nm. The comprehensive analysis conducted through diverse spectroscopic and microscopic techniques enhances our understanding of the synthesized silver nanoparticles. This research significantly contributes to the burgeoning field of green synthesis methods, showcasing P. bigalandulosa leaf extract as a promising and sustainable precursor. The detailed characterization is imperative for discerning the potential applications of these silver nanoparticles across various domains, particularly in the realms of biomedical and nanotechnology.